Irrigation and schistosomiasis in Africa: ecological aspects - Boelee, Eline; Madsen, H. (International Water Management Institute, 2006)
This research report discusses ecological aspects of schistosomiasis transmission and options for its control in irrigated areas in Africa through environmental measures. Human schistosomiasis is endemic in 46 African countries.After being infected by larvae emerging from human excreta and urine deposited in the water, freshwater snails act as intermediate hosts.